Contrasting lipid biomarker composition of terrestrial organic matter exported from across the Eurasian Arctic by the five great Russian Arctic rivers - van Dongen, B. E.; Semiletov, I.; Weijers, J. W. H.; Gustafsson, O. R. (Global Biogeochemical Cycles, 2008)
Surface sediments outside the great Russian Arctic rivers (GRARs; Ob, Yenisey, Lena, Indigirka, and Kolyma) were investigated for their lipid biomarker composition to elucidate compositional distinctions of the exported organic matter (OM) across this continent-scale climosequence of the Siberian Arctic. The lipid biomarker composition is dominantly terrestrial (high molecular weight (HMW) n-alkanols, n-alkanoic acids, n-alkanes; branched glycerol dialkyl glycerol tetraethers (GDGTs), beta-sitosterol, other sterols, and triterpenoids) with only minor marine contributions (e. g., the ratio of terrigenous-to-aquatic n-alkanes was 17-80, the TOC/TN ratio was 10-16, and the branched and isoprenoid tetraether (BIT) index > 0.88). There is a large contribution of C-23 and C-25 homologues relative to other long-chained n-alkanes, suggesting substantial contribution of probably Sphagnum-derived OM. The C-23 and C-25 contribution decreases eastward, signaling either a decrease in the potential contribution of Sphagnum or a shift within the n-alkane distribution of Sphagnum species or increased aeolian input, due to more arid conditions in the east. Other distinctions in molecular OM composition across the climosequence include increased concentrations of both HMW n-alkanoic acids and beta-sitosterol relative to HMW n-alkanes in the eastern sediments. This suggests that the OM exported by the eastern GRARs is, despite their higher bulk radiocarbon ages, less degraded, which is consistent with increasing permafrost and a shorter annual thaw period in eastern Siberia. Taken together, this benchmark study of the current composition of terrestrially exported OM suggests distinguishing continent-scale trends in molecular composition of the OM across the west-east set of GRARs, which reflects both differences in vegetation and climate. If the climate in the eastern Russian Arctic region becomes more like the current state in the western part, these results would predict a greater degree of decomposition of the old terrestrial OM released by the eastern GRARs and thus greater remineralization and release as CO2 and methane.
id: 819; 261FT Times Cited:10 Cited References Count:112Y